Peran Masyarakat Desa Sumberejo pada Penyelenggaraan Pilkada Serentak Tahun 2024 - Kusuma Widya Ningrum; Nur Aisah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this journal is to provide socialization and education to the people of Sumberejo Village about political violations and the role of society in organizing regional elections. Participatory supervision plays an important role in realizing democratic leaders. Community participation that takes part in this regional election can produce integrity, credibility of organizers, transparency of organizers and accountability of election results. The method used by students is to use the socialization method by inviting members of the KPU, the people of Sumberejo Village, the Sumberejo Village apparatus, the Sub-district Panwas, and the Sumberejo Village PPS. The communication tools used by students to deliver the material are using Powerpoint and Projectors. With this socialization, it is hoped that all elements of society and government can work together to carry out regional elections fairly and in a focused manner.